Evaluation of Polyvinylidene Fluoride (PVDF) integrated sensor for physiological temperature detection. (19th September 2022) - Schmidt, Devin; Mahapatro, Anil; Loflin, Ben; Cluff, Kim
ABSTRACT: In the human body, maintaining the core body temperature (CBT) is vital to ensure proper cellular and body functions. The temperature of 37°C (98°F) is the well-established baseline for CBT, but significant deviations to under 35°C (95°F) or over 40°C (104°F) can result in several health complications. If unnoticed in spaceflight, astronauts CBT could reach dangerously high levels when doing physically challenging tasks such as spacewalking or exercise. Therefore, a real-time multi-physiological parameter sensing system is needed to noninvasively monitor the status of crew members in space. The purpose of this paper is to test a novel temperature sensor developed by integrating thin sheets of polyvinylidene fluoride (PVDF), a temperature dependent dielectric material, into the sensor system designed as a substrate. This substrate interacts with the electromagnetic field created by the spiral sensor to result in a quantitative temperature monitoring sensor with a resolution of 1°C.